2022
DOI: 10.1111/cogs.13204
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Team Effectiveness by How Players Structure Their Search in a First‐Person Multiplayer Video Game

Abstract: People working as a team can achieve more than when working alone due to a team's ability to parallelize the completion of tasks. In collaborative search tasks, this necessitates the formation of effective division of labor strategies to minimize redundancies in search. For such strategies to be developed, team members need to perceive the task's relevant components and how they evolve over time, as well as an understanding of what others will do so that they can structure their own behavior to contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 103 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…In contrast, when no fog was present, ground players had a greater ability to perform tasks independently without the guidance of the operator, which then enabled a team’s search to be more like a parallel process. In recent work ( Nalepka et al, 2022 ), the challenges imposed by fog could be mitigated by giving direct access of the in-game map to the ground players – in this case, through a head-up display ( HUD ). This work demonstrated that when ground players are given a HUD, there was no impact of task visibility on team performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, when no fog was present, ground players had a greater ability to perform tasks independently without the guidance of the operator, which then enabled a team’s search to be more like a parallel process. In recent work ( Nalepka et al, 2022 ), the challenges imposed by fog could be mitigated by giving direct access of the in-game map to the ground players – in this case, through a head-up display ( HUD ). This work demonstrated that when ground players are given a HUD, there was no impact of task visibility on team performance.…”
Section: Discussionmentioning
confidence: 99%
“…Teams played a networked multiplayer game referred to as Desert Herding ( Nalepka et al, 2022 ). The task was inspired by previous research exploring corralling behaviors in two-person task contexts ( Nalepka et al, 2017 , 2019 , 2021b ; Rigoli et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations